2016
DOI: 10.1097/aog.0000000000001743
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes for Conversion to Laparotomy of Laparoscopic Hysterectomy in Benign Gynecology

Abstract: This analysis demonstrates that conversion to laparotomy is associated with increased odds of postoperative morbidity, and robotic assistance and surgeon volume are strongly associated with decreased odds of conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 19 publications
7
33
1
Order By: Relevance
“…Overall, almost 7,000 women underwent an attempted LH with 3.93% (n=275) converted to laparotomy. After adjusting for intra-operative associated-factors, hysterectomy indication, and socioeconomic differences, the authors observed a decreased odds of conversion to laparotomy with the use of robotic-assisted laparoscopy compared with conventional laparoscopy (adjusted odds ratio 0.14, 95% confidence interval 0.07–0.25) with a predicted risk of conversion of 0.8% compared with 5.4% ( P <0.001) 14 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Overall, almost 7,000 women underwent an attempted LH with 3.93% (n=275) converted to laparotomy. After adjusting for intra-operative associated-factors, hysterectomy indication, and socioeconomic differences, the authors observed a decreased odds of conversion to laparotomy with the use of robotic-assisted laparoscopy compared with conventional laparoscopy (adjusted odds ratio 0.14, 95% confidence interval 0.07–0.25) with a predicted risk of conversion of 0.8% compared with 5.4% ( P <0.001) 14 .…”
Section: Discussionmentioning
confidence: 95%
“…These results are in agreement with previous studies, which showed lack of evidence of RH benefits over other conventional techniques for benign uterine conditions but did show greater costs 1 , 12 , 13 . However, there was one study, by Lim et al 14 , that estimated the incidence and reasons for conversion to laparotomy in women submitted to LH for benign gynecologic indications. Overall, almost 7,000 women underwent an attempted LH with 3.93% (n=275) converted to laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this may become valid in some particular settings such as those with less laparoscopic expertise. To note, Lim et al . (2016) recently reported the rate of conversion was lower with robotic surgery when referring to a general community-based sample of gynecologic surgeons.…”
Section: The 10 ‘Don’ts’ In Endometriosis Managementmentioning
confidence: 99%
“…19 The conversion rate from laparoscopic to open hysterectomy for benign cases might be as high as 19%. 20 Reported risk factors for conversion include increasing age, BMI, history of previous abdominopelvic surgery, adhesive disease, endometriosis, leiomyomata, uterine weight, and low-volume surgeons. 20 A retrospective cohort analysis of a multicenter Michigan database of almost 7000 women undergoing benign hysterectomy found a sevenfold reduction in the odds of conversion to laparotomy with use of the robotic platform compared to conventional laparoscopy.…”
Section: Robotic Surgery Outcomesmentioning
confidence: 99%